Mechanism of sarcoplasmic reticulum Ca-ATPase and multidrug resistance P-glycoprotein probed by Pi-HOH oxygen exchange - Seekoe, Tshepo W (Division of Chemical Pathology, 2014)
Bibliography: leaves 135-146.